Case Study on Solving Soil Problem by Using Various Chemical Additives in Foundation - Khalid, Nurul Ainul Hamizah Binti; Lim, Alvin John Meng Siang (Recent Trends in Civil Engineering and Built Environment, 2021)
This work aimed to study the most effective chemical additives to increase the strength of the clay soil. The case study was for the clay soil, and the problem statement was to improve the clay soil strength to avoid failure in the ground. These chemical additives were commonly used to stabilize the soil and make the shear strength of the soil increase. The chemical additives that be used are lime, cement, and fly ash. The percentage of the chemical additive used in the soil mixture was 8% to 10%. The data taken was from the previous research, where the data was compared to get the most effective chemical additives to improve the soil stability and soil strength. Data were collected through 30 previous studies using clay and chemical additives such as cement, lime, and fly ash. The data for Plastic Limit, Liquid Limit, Plasticity Index, Optimum Moisture Content, Maximum Dry Density, and Unconfined Compressive Strength was taken by referring to the previous study. Then the data was listed in Microsoft Excel to generate the graph for comparison. All the data obtained are then compared to get which chemicals can increase the strength of the soil. The result of this study is the most effective chemical additives is with lime which can increase the strength of the soil. Therefore, failure in the foundation can be avoided.